Immunoassays Based on Penicillium marneffei Mp1p Derived from Pichia pastoris Expression System for Diagnosis of Penicilliosis - Yanfang Wang; Jian‐Piao Cai; Yadi Wang; Hui Dong; Wei Hao; Lingxiao Jiang; Jun Long; Che-Man Chan; Patrick C. Y. Woo; Susanna K. P. Lau; Kwok‐Yung Yuen; Chi‐Ming Che (2011)
Background Penicillium marneffei is a dimorphic fungus endemic in Southeast Asia. It can cause fatal penicilliosis in humans, particularly in HIV-infected people. Diagnosis of this infection is difficult because its clinical manifestations are not distinctive. Specialized laboratory tests are necessary to establish a definitive diagnosis for successful management. We have demonstrated previously that a cell wall mannoprotein Mp1p, abundant in P. marneffei, is a potential biomarker for diagnosis of P. marneffei infections. In the present study, we describe immunoassays based on Mp1p derived from the yeast Pichia pastoris expression system. Methodology/Principal Findings We generated monoclonal antibodies (MAbs) and rabbit polyclonal antibodies (PAbs) against Mp1p expressed in P. pastoris. Subsequently, we developed two Mp1p antigen capture ELISAs which employed MAbs for both the capture and detecting antibodies (MAb-MAb pair) or PAbs and MAbs as the capture and detecting antibodies (PAbs-MAb pair) respectively. The two Mp1p antigen ELISAs detected Mp1p specifically in cultures of P. marneffei yeast phase at 37–40°C and had no cross-reaction with other tested pathogenic fungi. The sensitivities and specificities of the two antigen assays were found to be 55% (11/20) and 99.6% (538/540) for MAb-MAb Mp1p ELISA, and 75% (15/20) and 99.4% (537/540) for PAbs-MAb Mp1p ELISA performed using 20 sera with culture-confirmed penicilliosis, and 540 control sera from 15 other mycosis patients and 525 healthy donors. Meanwhile, we also developed an anti-Mp1p IgG antibody ELISA with an evaluated sensitivity of 30% (6/20) and a specificity of 98.5% (532/540) using the same sera. Furthermore, combining the results of Mp1p antigen and antibody detection improved the sensitivity of diagnosis to 100% (20/20). Conclusions/Significance Simultaneous detection of antigen and antibody using the immunoassays based on Mp1p derived from P. pastoris greatly improves detection sensitivity. The procedures should be useful for the routine diagnosis of penicilliosis.